Model of Non-uniform Application of the Common External Tariff in the EC - Carsten Weerth (Global Trade and Customs Journal, 2009)
Many legal advisers, scientists and practitioners know since many years, that the Common External Tariff (CET) of the European Community (EC) is being applied non-uniform from the different national customs services and that the economic operators are using this systematic fault of the EC for their advantage. Which forms of advantages of price differences according to different duty rates at market entry into the EC common market are there? A model of non-uniform application of the CET of the EC has been developed and proven during three years of research and is presented in this paper.
Additional information: Self-archiving of author's post-print (accepted paper) for scientific use only on personal page in RePec (e.g. https://authors.repec.org) according to publishers policies as documented on SHERPA/ROMEO database under URL: http://www.sherpa.ac.uk/romeo/issn/1569-755X/en//. Copyright-holder is Kluwer Law International.
Keywords: K33; K34; F53; 330; Customs Law; European Union; European Law; Customs Union